A Common NLRC4 Gene Variant Associates With Inflammation and Pulmonary Function in Human Immunodeficiency Virus and Tuberculosis. (22nd November 2019) - Ravimohan, Shruthi; Maenetje, Pholo; Auld, Sara C; Ncube, Itai; Mlotshwa, Mandla; Chase, William; Tiemessen, Caroline T; Vangu, Mboyo-Di-Tamba; Wallis, Robert S; Churchyard, Gavin; Weissman, Drew; Kornfeld, Hardy; et al.
Abstract: Background: Inflammasomes mediate inflammation in adults living with both human immunodeficiency virus (HIV) and tuberculosis (TB), but the relevance of inflammasome gene polymorphisms in TB-associated pulmonary damage is unknown. We hypothesized that functional single-nucleotide polymorphisms (SNPs) in inflammasome pathway genes modify systemic and pulmonary inflammation, contributing to respiratory impairment in adults living with HIV/pulmonary TB. Methods: This was a prospective cohort study set in South Africa following individuals living with HIV/TB up to 48 weeks post-antiretroviral therapy (ART) initiation. Ten functional SNPs in 5 inflammasome pathway genes were related to circulating inflammatory biomarkers and lung function assessed by spirometry pre- and post-ART initiation. Analyses used 2-sided t tests, Wilcoxon rank sum tests, Spearman correlation coefficients, linear regression, and generalized estimating equation models. Results: Among 102 patients with baseline samples, the minor allele (T) in NLRC4 rs385076 was independently associated with lower levels of interleukin (IL)-18 and IL-6 before and up to 12 weeks post-ART initiation (Benjamini-Hochberg corrected P values < .02). Patients with the CT/TT genotypes also had improved lung function vs CC patients up to 48 weeks post-ART initiation (forced vital capacity, 206 mL higher; 95% confidence interval [CI], 67–345 mL; P = .004 and forced expiratory volume in 1 second, 143 mL higher; 95% CI, 11–274 mL; P = .034). Conclusions: A common SNP in the NLRC4 inflammasome may modify TB-associated inflammation in clinically relevant ways. This SNP may identify high-risk groups for lung damage in TB. Inhibition of NLRC4 activity may be an important approach for TB host-directed therapy. Abstract : In this study, a common polymorphism in an inflammasome gene was associated with lower inflammatory biomarker levels and more preserved lung function in adults living with both human immunodeficiency virus and pulmonary tuberculosis (TB). Therapies that target inflammasomes may be beneficial to pulmonary health in TB.